Financial Performance Information System Using Economic Value Added Method - Fahrian, Arris; Nasution, Muhammad Irwan Padli (Information Technology and Science (ITScience), 2023)
In the current era of globalization, information is needed in a management organization. Most companies prefer computerized information systems because they simplify performance management. The rapid development of today's technology is also very useful and supports all aspects of life, especially in managing accounting and financial information systems, becoming a financial analysis of a company as a benchmark in assessing company performance. At the place where this research was carried out, there was no financial data to measure financial management performance. Become a reference in evaluating financial reports to assess financial performance in this study. Responding to these problems, it can be formulated to design a financial performance information system by applying the web-based EVA (Economic Value Added) method to assess whether a company's financial performance measurement influences growth or decline for decision makers related to financial management. and investors and provide results to company stakeholders as an evaluation value of financial management. The end result of this research is the EVA value for the company is Rp. 4,267,398,060. And this value can be used as an evaluation of management at the research site.